Effect of Partial Replacement of Concentrate Feed with Moringa Leaves (Moringa oleifera) on Performance of Growing Pigs - R.K, Sowjanya Lakshmi; Ch, Venkata Seshiaha; M, Kalyan Chakravarthy; M, Dharma Rao; K, Sireesha; T, Susmita (Indian Journal of Animal Nutrition, 2020)
An experiment was conducted to study the effect of feeding Moringa oleifera leaves on growth performance, haematology and serum metabolite profile of growing SVVU T-17 breed of pigs. Twelve grower pigs of three months of age were divided into two groups of six each based on body weights (28 kg). Animals were fed with control (T1) and treatment (T2) diets for a period of 14 weeks. T1 group pigs received 100% dry matter (DM) requirement as a standard pig grower (maize and soya based) feed while T2 group pigs received only 70% of their daily DM requirement as grower feed and 30% of their requirements were met through fresh moringa leaves. There was no significant (P>0.05) effect of replacement of 30% of concentrate feed with moringa leaves on body weight gains, haematology and serum biochemistry of growing pigs. Cost per kg of body weight was reduced from â‚¹ 84.80 (T1) to â‚¹ Rs. 64.78 (T2) by replacing 30% concentrate with fresh moringa leaves.Â Thus, fresh Moringa leaves can be fed upto 30% in the diets of grower pigs for economic pig production.